INDUSTRIAL TOURISM IN GERMANY : SITUATION , WEAKNESES AND CHALENGES - Dietrich Soyez (Geography, Environment, Sustainability)
Industrial tourism, i.e. visiting both active and historic industrial plants (or their historical remains), has been a growing sector in tourism for years, but is nevertheless unlikely to lose its “niche” character... Today it is generally offered under the general heading of cultural tourism, and in this context is often also marketed as active or adventurous tourism (and associated with educational aims), both in marked contrast to the traditional relaxing holiday. The forms of supply and demand that have developed in industrial tourism are of growing significance both for historic and active industrial regions, as suchtourism can provide very positive stimuli for structural policy, regional economies and reputations. Recently, remarkable industrial tourism destinations (industrial Brand Worlds) have emerged both in the old industrialised countries of Europe and North America andin Newly Industrialising Countries/NICs, e.g. in Asia. Many of these destinations need notfear comparison with the attractiveness of classical destinations for national or eveninternational tourism, and a few leading industrial sites already have impressive visitor numbers.After a brief overview of the current state of supply and demand in industrial tourism inGermany, the following points will form the focus of the analysis:–– Suppression of controversial and darkaspects of industrialisation (especially intimes of war, annexation and occupation)–– Innovations (particularly in the formof so-called Brand Worlds, e.g. in theautomobile industry).